2015
DOI: 10.1515/hf-2014-0362
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fire retardants based on N and P and poly(sodium silicate-aluminum dihydrogen phosphate) (PSADP) and testing the flame-retardant properties of PSADP impregnated poplar wood

Abstract: The development of fire retardants (FRs) is an approximative process of optimization. In this context, a novel water-soluble formulation with poly(sodium silicate-aluminum dihydrogen phosphate) (PSADP) has been developed, aiming at reduced hygroscopicity and enhanced leaching resistance of poplar wood in combination with nitrogen-phosphorus (NP) FR (FRNP). After treatment of wood with FRNP and PSADP in vacuum, the following data of the samples were determined: rate of hydroscopicity, leaching resistance, heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The consolidation effect of the polymer resins is significantly improved by the nanodispersion in these solutions of mineral materials with reinforcing effect (especially metal oxides) [37]. The nanoinsertions of these nanocomposites into the wood support, besides the role of physical consolidation, also provide an important increase in resistance to oxidative and biological degradation (fungus mildew) and increased flame retardancy [38][39][40][41]. The most suitable polymers for wood preservation are aliphatic and aliphatic epoxy acrylic resins due to their stability to oxidative degradation, their adhesion, and processability.…”
Section: Historical Wood Artifacts Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…The consolidation effect of the polymer resins is significantly improved by the nanodispersion in these solutions of mineral materials with reinforcing effect (especially metal oxides) [37]. The nanoinsertions of these nanocomposites into the wood support, besides the role of physical consolidation, also provide an important increase in resistance to oxidative and biological degradation (fungus mildew) and increased flame retardancy [38][39][40][41]. The most suitable polymers for wood preservation are aliphatic and aliphatic epoxy acrylic resins due to their stability to oxidative degradation, their adhesion, and processability.…”
Section: Historical Wood Artifacts Conservationmentioning
confidence: 99%
“…Systems containing both phosphorous and nitrogen components are good substitutes for halogenated FR due to their synergistic effect [38,39]. In [40], nitrogen-phosphorous FR dispersed in poly(sodium silicate-aluminum dihydrogen phosphate) (PSADP) was used to reduce poplar wood hygroscopicity and to improve its fire resistance. These two components present a synergic effect on the two properties being distributed over the inner surface and penetrate the cell cavities of wood.…”
Section: Main Absorption Bands CM −1mentioning
confidence: 99%
“…Many studies have used different modification processes, including acetylation, fire retardants, preservatives, impregnation with resins, as well as heat treatment, to improve wood performance (Esteves and Pereira 2009;Hamdan and Islam 2012;Ajdinaj et al 2013;Adebawo et al 2015;Kumar et al 2015;Zhang et al 2015). Unlike other modifications, heat treatment is one of the oldest and most environmentally friendly, and it has recently received renewed interest because of the limitations on the use of natural lumber and restrictive regulations on the use of toxic chemicals (Hillis and Rozsa 1985;Boonstra et al 2006a,b).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the compression was mostly in the surface layer (about 3 mm). It has been reported that the NP has a catalytic dehydration effect on wood polysaccharides during HT [32], and this could also make the wood surface layer more likely to be compressed because of the softening effect at higher moisture and temperature conditions [25]. From NP fire retardants can be produced softener-NH 3 , which reduces glass transition temperature of lignin, i.e., decrease Tg from approximately 170 • C [39].…”
Section: Properties Of the Functionalized Surface Layermentioning
confidence: 99%